2016
DOI: 10.1142/s0217751x16500214
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dark matter and the scalar-tensor model

Abstract: The relic abundance of asymmetric Dark Matter particles in the scalar-tensor model is analyzed in this article. We extend the numeric and analytic calculation of the relic density of the asymmetric Dark Matter in the standard cosmological scenario to the nonstandard cosmological scenario. We focus on the scalar-tensor model. Hubble expansion rate is changed in the nonstandard cosmological scenario. This leaves its imprint on the relic density of Dark Matter particles. In this article we investigate to what ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
(32 reference statements)
2
18
1
Order By: Relevance
“…However these studies are based upon the enhancement factor (1.2) and also neglect the temperature dependence of g * (T ). Unsurprisingly, our results are much less dramatic than those given by Gelmini et al [9] and Wang et al [30] who found that the required annihilation cross section can be increased by several orders of magnitude.…”
Section: Asymmetric Dark Mattercontrasting
confidence: 77%
See 2 more Smart Citations
“…However these studies are based upon the enhancement factor (1.2) and also neglect the temperature dependence of g * (T ). Unsurprisingly, our results are much less dramatic than those given by Gelmini et al [9] and Wang et al [30] who found that the required annihilation cross section can be increased by several orders of magnitude.…”
Section: Asymmetric Dark Mattercontrasting
confidence: 77%
“…To complete our study we also investigated the relic abundance of asymmetric dark matter species in scalar-tensor gravity models and found that the required annihilation cross section was enhanced only slightly, in contrast to the several order of magnitude estimates given in Gelmini et al [9] and Wang et al [30] who both used the parameterization (1.2) given in Catena et al [28].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Usually the indirect detection is not available for the asymmetric Dark Matter. However, for asymmetric Dark Matter in nonstandard cosmological scenarios including quintessence, scalar-tensor model and brane world cosmology [9,10,11], the relic densities for both particle and antiparticle are increased in due to the enhanced Hubble expansion rate. Again for appropriate cross section, the relic density for both particle and anti-particle are almost in the same amount which is different from the standard cosmological scenario where the anti-particle relic density is depressed .…”
Section: Constraints On Parameter Spacementioning
confidence: 99%
“…The modified Hubble expansion rate affects the relic density of asymmetric Dark Matter. The asymmetric Dark Matter relic density is already investigated in such models including quintessence model, scalar-tensor model [9,10,11]. In quintessence model, scalar-tensor models, the relic densities of both particles and anti-particles are increased simultaneously due to the increased Hubble expansion rate.…”
Section: Introductionmentioning
confidence: 99%